Saṭīka va sacitra śivarāja-bhūṣaṇa : alaṅkāra-grantha - Bhūṣaṇa ((Rājā) Rāmakumāra Bukaḍipo uttarādhikārī Navalakiśora-Presa, Bukaḍipo, 1951)
Verswerk über die Dichtkunst. - Hindi poetry presenting episodes from life of Raja Shivaji, 1627-1680